High Energy Density Lithium–Sulfur Batteries: Challenges of Thick Sulfur Cathodes. Issue 16 (9th March 2015) - Lv, Dongping; Zheng, Jianming; Li, Qiuyan; Xie, Xi; Ferrara, Seth; Nie, Zimin; Mehdi, Layla B.; Browning, Nigel D.; Zhang, Ji‐Guang; Graff, Gordon L.; Liu, Jun; Xiao, Jie
<x xml:space="preserve">Abstract</x> High energy and cost‐effective lithium sulfur (Li–S) battery technology has been vigorously revisited in recent years due to the urgent need of advanced energy storage technologies for green transportation and large‐scale energy storage applications. However, the market penetration of Li–S batteries has been plagued due to the gap in scientific knowledge between the fundamental research and the real application need. Here, a facile and effective approach to integrate commercial carbon nanoparticles into microsized secondary ones for application in high loading sulfur electrodes is proposed The slurry with the integrated particles is easily cast into electrode laminates with practically usable mass loadings. Uniform and crack‐free coating with high loading of 2–8 mg cm−2 sulfur are successfully achieved. Based on the obtained thick electrodes, the dependence of areal specific capacity on mass loading, factors influencing electrode performance, and measures used to address the existing issues are studied and discussed.